2021
DOI: 10.7717/peerj-cs.598
|View full text |Cite
|
Sign up to set email alerts
|

Towards generalisable hate speech detection: a review on obstacles and solutions

Abstract: Hate speech is one type of harmful online content which directly attacks or promotes hate towards a group or an individual member based on their actual or perceived aspects of identity, such as ethnicity, religion, and sexual orientation. With online hate speech on the rise, its automatic detection as a natural language processing task is gaining increasing interest. However, it is only recently that it has been shown that existing models generalise poorly to unseen data. This survey paper attempts to summaris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(68 citation statements)
references
References 90 publications
(266 reference statements)
1
39
0
Order By: Relevance
“…There has also been a significant amount of criticism regarding the application of machine learning to conversation moderation, see [36] for a recent survey of the issues and challenges. The nature of online identity and social relationships, and the problems of governance are complex and involve many interacting entities with overlapping jurisdictions.…”
Section: Related Workmentioning
confidence: 99%
“…There has also been a significant amount of criticism regarding the application of machine learning to conversation moderation, see [36] for a recent survey of the issues and challenges. The nature of online identity and social relationships, and the problems of governance are complex and involve many interacting entities with overlapping jurisdictions.…”
Section: Related Workmentioning
confidence: 99%
“…However, the study of biases based on psychographic attributes (grouping individuals w.r.t their beliefs and interests) is yet to gain popularity. Note that unlike the majority of literature on toxic speech, we do not limit our toxic speech taxonomy to the demographic attributes of a group or an individual [99]. Rather, we encourage future exploration of bias categories tied with psychographic attributes.…”
Section: Categories Of Biasmentioning
confidence: 99%
“…We do not survey all the existing toxicity detection methods; instead, we focus on a subset of them exploring and mitigating bias in toxic speech detection. Meanwhile, Yin and Zubiaga [99] surveyed the literature addressing the robustness of hate speech detection methods and addressed the subject of bias in hate speech detection as well. While their discussion remained general commentary, we aim to develop an extensive understanding of these methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Substantial experiments by Fortuna et al [34] showed that training with one data set and testing with another one can decrease the performance by over 30%. Many potential reasons can be seen as obstacles for the generalisability [35,36,37,38] such as dataset size and annotation quality. However, little is known about their effects.…”
Section: Reliability Of Data Setsmentioning
confidence: 99%